Bronzezeitliche und Eisenzeitliche Gefäße aus Zypern. Protoattische und attisch-geometrische Keramik Kunsthistorisches Museum Wien 6 - Lang-Auinger, Claudia (Verlag der Österreichischen Akademie der Wissenschaften, 2019)
The Cypriote collection of complete vessels - nine of them belong to the late Bronze Age, 126 to lron Age - are presented in this volume.20 objects of Attic-Geometric and Protoattic pottery are attached to the Cypriote pottery. The particular interest of this small collection with some outstanding pieces is the close connection to Alexander Conze, professor of archaeology at Vienna, pioneering the study of the Geometrie style in the early 1870s.